Penerapan Hardening Server Linux untuk Meningkatkan Keamanan Sistem Messaging IoT - Hartanto, Agus; Margaretta Huizen, Lenny; Firman Daru, April; Surono, Surono (Jurnal Transformatika, 2026)
Linux-based servers are extensively utilized as core infrastructure for network services, particularly as IoT Messaging Servers based on the MQTT protocol. However, many servers remain vulnerable to security breaches due to misconfigurations or unpatched flaws. This study aims to implement and analyze the effectiveness of Linux server hardening in enhancing system security against network-based attacks. The research was conducted using Ubuntu Server 22.04 running Mosquitto MQTT within a virtualized environment, employing a limited penetration testing approach. Testing scenarios were focused on port scanning, brute-force authentication attacks, and unauthorized access to MQTT services, excluding kernel-level or zero-day exploits. The hardening methodology encompasses system updates, SSH configuration hardening, user management, UFW firewall implementation, Fail2ban integration, Mosquitto-specific hardening, and security log monitoring. Security indicators were measured based on the reduction of open ports, the success rate of automated brute-force blocking, and the improvement in logging quality. The results demonstrate a reduction in vulnerability exposure by up to 75% and a significant improvement in security detection and response. This research contributes a novel measurable integration between hardening automation, firewalling, and IoT applications, thereby minimizing the risk of exploitation vulnerabilities.